Near-infrared optical response and carrier dynamics for high photoconversion power in tellurene - Villegas, Cesar E. P. (2022)
Materials for applications in solar cells require a combination of features including an appropriate band gap and long relaxation times for photoexcited hot carriers. On the basis of ab initio many-body perturbation theory, including the spin–orbit interaction, we investigate the photocarrier generation and dynamics in α-tellurene. We show that photoexcited electrons are mainly generated in the near-infrared range, starting at 0.89 eV and forming excitons that are strongly bound, compared to its bulk counterpart, with a binding energy of 0.31 eV. We also explore the role of the electron–phonon interaction, finding that the electronic states in the first conduction band minimum couples weakly with phonons, yielding longer hot electron lifetimes (up to 70 fs) and mean free paths up to 37 nm. We also show that the extraction of hot holes may result in a challenging task as these carriers possess sub-3 nm mean free paths. We finally estimate that 1-nm-thick α-Te provides a short-circuit current density of 6.7 mA/cm2 and a maximum power conversion efficiency of 4.4%, which highlights its potential for efficient photovoltaic device development.